(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this paper, we present a numerical physical splitting approach ¬using the Fourier transform (SSFT) to solve the one-dimensional nonlinear Schrödinger equation (NLSE) that includes the fiber loss term. Although this basic equation defines the propagation of a pulse in a loss fiber, it is not supported by an accurate analytical solution. Based on this, the MATLAB numerical results confirm that the physical splitting numerical approach ¬using the Fourier transform (SSFT) demonstrates superior performance compared to other proposed schemes in simulating the propagation of solitons in a loss optical fiber.